Anti-Money Laundering and Combating the Financing of Terrorism : Observations from the Work Program and Implications Going Forward. (Policy Papers; Policy Paper ;, 2005)
The first part presents the findings concerning overall compliance with the revised standard and methodology and the second part compares these findings to those of assessments under the old methodology. The third part discusses interpretative and application issues and the fourth describes logistical issues based on the experience of the assessments carried out to date.